INFLUENCE OF HYDROPHOBIZING ADDITIVES ON THE THERMAL PROPERTIES OF LIGHTWEIGHT CASES LOCATED IN AN AGGRESSIVE ENVIRONMENT (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article deals with the effect of hydrophobizing additives on the thermophysical properties of expanded clay concrete.